Seroprevalence and Transmission of Human Influenza A(H5N1) Virus before and after Virus Reassortment, Cambodia, 2006–2014 - Sowath Ly; Paul F. Horwood; Malen Chan; Sareth Rith; Sopheak Sorn; Kunthea Oeung; Kunthy Nguon; Siam Chan; Phalla Y; Amy Parry; Reiko Tsuyuoka; Sovann Ly; et al. (Emerging Infectious Diseases, 2017)
Thirty-five human influenza A(H5N1) cases were reported in Cambodia during 2013–2014 after emergence of a clade 1.1.2 reassortant virus. We tested 881 villagers and found 2 cases of pauci- or asymptomatic infection. Seroprevalence after emergence of the reassortant strain (0.2%) was lower than the aggregate seroprevalence of 1.3% reported in earlier studies.